A BRIEF APPROACH ON TEACHING-LEARNING PROCEDURES AND SOFTY SKILLS IN CIVIL ENGINEER TRAINING (Interdisciplinary Studies Journal, 2024)
With the intention of sparking students' interest and positioning them as protagonists in the teaching-learning process, there has been an increasing investment in the implementation of new pedagogical approaches. In addition to technical and academic skills, it is essential for students to develop social and personal skills, known as soft skills. In this context, this study aims to explore different active teaching-learning methodologies and emphasize the relevance of interpersonal skills in the formation of civil engineers. Moreover, concepts related to the use of technologies and their contributions to the advancement of education are discussed. The methodology used consists of developing a theoretical foundation based on bibliographic and documentary research. This research concludes that the application of different teaching-learning strategies, combined with the use of technology, can enhance student motivation, facilitate the understanding of civil engineering content, and foster their active engagement in the learning process, an essential factor for their professional development. The relevance of soft skills, fundamental interpersonal and behavioral abilities for employability in the contemporary job market, is also emphasized. These competencies have become increasingly valued by companies, which seek professionals capable of adapting and collaborating in dynamic and challenging environments.
Keywords: Active Methodologies; Technology in Teaching; Civil Engineering Education; Soft Skills